Use of Telemetry Blood Pressure Transmitters to Measure Intracranial Pressure (ICP) in Freely Moving Rats - Silasi, Gergely; MacLellan, Crystal L.; Colbourne, Frederick (Current Neurovascular Research, 2009)
Stroke and traumatic brain injuries often lead to cerebral edema and persistent elevations in intracranial pressure (ICP) that can be life threatening. Thus, rodent models would benefit from a simple and reliable method to measure ICP in awake, mobile animals. Up to now most techniques have been limited to anesthetized or immobile animals, which is not practical for following the prolonged elevations in ICP that follow stroke and traumatic brain injury. With an initial set of data, we describe a simple method that uses blood pressure telemetry sensors, which are commercially available (Data Sciences Int.) to measure ICP in freely moving rats for several days following implantation. Basically, an epidural cannula is secured to the skull and connected to the catheter of the telemetry probe, which is then secured inside a protective plastic shield on the skull. We confirm the sensitivity of our measurements by experimentally modifying ICP by either the Valsalva maneuver (abdominal compression) or a large ischemic brain injury. The Valsalva maneuver caused a small brief spike in ICP (lasting about 2-3 sec), whereas a transient middle cerebral artery occlusion substantially increased ICP (up to 50 mmHg) for approximately 3 days post-surgery. In summary, the current method allows for ICP to be continuously monitored in rats for several days, and thus is suitable for studies investigating mechanisms of raised ICP and in testing experimental treatments that mitigate it.
Keywords: ischemia